Activity of Trichoderma asperellum Strain ICC 012 and Trichoderma gamsii Strain ICC 080 Toward Diseases of Esca Complex and Associated Pathogens - Di Marco, Stefano; Metruccio, Elisa Giorgia; Moretti, Samuele; Nocentini, Marco; Carella, Giuseppe; Pacetti, Andrea; Battiston, Enrico; Osti, Fabio; Mugnai, Laura (Frontiers in Microbiology, 2022)
Grapevine trunk diseases are widespread in all grape-growing countries. The diseases included in the Esca complex of diseases are particularly common in European vineyards. Their distinctive foliar symptoms are well known to be associated not only with losses in quantity, as with all grapevine wood diseases, but also with losses in the quality of the crop. Protection of pruning wounds is known to reduce infections in artificial inoculations and, to some extent, reduce the external leaf symptoms. The application of biological control agents in the field is typically started at the first appearance of symptoms. In this article, the two strains belonging to two different species, Trichoderma asperellum ICC 012 and T. gamsii ICC 080, which are present in a commercial formulation, were tested in vitro, in vivo in artificial inoculation, and in the field in long-term experiments where the wounds on four young asymptomatic vineyards were protected since 1 or 2 years after planting. The in vitro trials highlighted the different temperature requirements of the two strains, the direct mycoparasitizing activity of T. asperellum, and the indirect activity shown by both Trichoderma strains. The in vivo trials confirmed the ability of the two strains to reduce the colonization following artificial inoculations with the high, unnatural concentration of spores used in artificial infections, even if with variable efficacy, and with long persistence as they could be reisolated 7 months post-application. The preventive applications carried out over 9 years showed a very high reduction in symptom development in the treated vines, on annual and cumulated incidence and on the death of vines, with disease reduction varying from 66 to almost 90%. Early and annual application of protection to the pruning wounds appears to be the best method for reducing damages caused by grapevine leaf stripe disease (a disease of the Esca complex of diseases). Trichoderma appears to offer an efficient, environmentally friendly, and long-lasting protection in the presence of a natural inoculum concentration.